Pelatihan Pengenalan Kesehatan dan Keselamatan Kerja di Laboratorium Kimia bagi Siswa SMK Cendekia Madiun - Ade Trisnawati; Churnia Sari; Kelik Sussolaikah (STIKes Ibnu Sina Ajibarang, 2023)
Occupational Health and Safety (K3) training aims to increase students' knowledge of working in the laboratory, identify potential hazards, and take early action if a hazard occurs in the laboratory. The target audience for this activity is class X students majoring in multimedia at SMK Cendekia, Madiun. This training was conducted in the Chemical Engineering Laboratory, Departemen of Chemical Engineering, Faculty of Engineering, Universitas PGRI Madiun. The methods used in the training are lectures, discussions, and practice in the chemistry laboratory. The data obtained from the K3 knowledge questionnaire before and after the training were analyzed descriptively. The results obtained show an increase in the average score of students from 46 to 67, which means that there is an increase in knowledge about OSH in the chemistry laboratory.